Advancing Energy Policy Lessons on the integration of Social Sciences and Humanities - Foulds, Chris; Robison, Rosie (Springer Nature, 2018)
This open access book advocates for the Social Sciences and Humanities to be more involved in energy policymaking. It forms part of the European platform for energy-related Social Sciences and Humanities' activities, and works on the premise that crossing disciplines is essential. All of its contributions are highly interdisciplinary, with each chapter grounded in at least three different Social Sciences and Humanities disciplines. These varying perspectives come together to cover an array of issues relevant to the energy transition, including: energy poverty, justice, political ecology, governance, behaviours, imaginaries, systems approaches, modelling, as well as the particular challenges faced by interdisciplinary work. As a whole, the book presents new ideas for future energy policy, particularly at the European level. It is a valuable resource for energy researchers interested in interdisciplinary and society-relevant perspectives. Those working outside the Social Sciences and Humanities will find this book an accessible way of learning more about how these subjects can constructively contribute to energy policy. ;